Analysis of Exports, Imports, Exchange Rates, and Inflation on Economic Growth in 5 ASEAN Countries (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study uses a quantitative associative approach to analyze the influence of exports, imports, inflation, and exchange rates on economic growth in five ASEAN member countries: Indonesia, Malaysia, Singapore, Thailand, and Vietnam. The data used are secondary data obtained from the World Bank for the period 2013–2023. The analysis technique used is the Panel Autoregressive Distributed Lag (Panel ARDL) Model, which begins with stationarity and cointegration tests. Results The ARDL Panel Model estimation in this study is declared valid because it meets the main requirements, namely having a cointegrated lag with a negative coefficient value of -0.831550 and significant at the 5% significance level (probability 0.0000 < 0.05). The long-term estimation results indicate that only the inflation variable has a significant influence on Gross Domestic Product (GDP) in the 5 ASEAN countries studied. Meanwhile, in the short term, no variables were found to have a significant influence on GDP in the 5 countries. Furthermore, country-level estimations show varying results. Indonesia is the only country that shows a significant influence of exports, imports, inflation, and exchange rates on GDP. Thailand shows a significant influence of exports and exchange rates, while Malaysia, Singapore, and Vietnam do not show any significant influence of exports, imports, inflation, and exchange rates on GDP. These findings reflect that the relationship between macroeconomic variables and economic growth in ASEAN countries is heterogeneous and is strongly influenced by the structural characteristics of each country.